The Sediment Accumulated Volume in the Reservoir Effected Agricultural Production - VONGCHANKEO, Sommone; SAYPANYA, Phetyasone; NOUANTHALONGSY, Sounthone (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The purpose of this study is to evaluate the amount of sediment in the water reservoir and to evaluate the effect on the agricultural area of the change of water volume in the water reservoir at the Nam Houm watershed, Naxaythong district, Vientiane capital. The results of the study found that: Total erosion or soil lost volume amount 4,295,530.03 m3 and basin floor have some sediment volume about 1,610,807.19 m3, sediment scatter area has 297.352 ha, with 34.522 % of the water surface and inclusion with 1.076% of the Namhoum watershed; Also results of the study found that the water requirement, water in the basin and the balance of water compared to the area like: the water demand of rice paddy in one season is supply required 13,928.96m3/ha/season, irrigated diversified crop or maize irrigation water requirement is supply required 3,014.172m3/ha/season and fish pound is supply required 2,000m3/ha/season, In the water volume amount 10x106 m3 supply for the rice paddy area of 717.93ha/season, supply for the diversified crop area of 3,317.66 ha/season, supply for the fish pound area of 2,000 ha/season and supply for the produced simultaneously area 270.69 ha/season. The efficiency of water supply to the production area decreased by 6.30% it there is some sediment volume in the basin with 1,610,807.19 m3.